Therapeutic strategies for atherosclerosis and atherothrombosis: Past, present and future - Weber, Christian; Badimon, Lina; Mach, Francois; van der Vorst, Emiel P. C. (Thrombosis and Haemostasis, 2017)
Even two centuries after they were first described, atherosclerosis and atherothrombosis remain among the leading causes of death worldwide. Over the last decades it has become clear that atherosclerosis is not only a lipid-driven disease but also a multifactorial process largely driven by inflammatory mediators, an insight that has instigated additional research and drug development focussing on anti-inflammatory therapies. In this review, we will provide a brief historical overview, followed by a more general synopsis of the range of currently available state-of-the-art therapies for atherosclerosis and atherothrombosis. Finally, we will highlight some of the promising therapeutic strategies that are currently under intense investigation. We believe that the next years will witness highly interesting developments and clinical trials investigating yet more novel therapies, and at the same time looking into potential combinations of all available therapies. This prospect closes in on the ultimate goal, which is to reduce the residual risk that still persists despite present therapeutic options.
Keywords: Atherosclerosis; atherothrombosis; therapeutic strategies